(3JfGSb GdOQQ aj JfGSH GdShQs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s ((3GdeDdas)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj GfRd cJGHg GdeLjO hHYO aEf Gddg SHMGfg hdg GdMeO ef Ydj HGdfXQ aj ehGbY fLheg haJM dj CHhGH GdfXQ Edi GSJNQGL eG ChOY ajg ef Ydheg hSejJg JfGSb GdOQQ aj JfGSH GdShQs
(3BNQgG (B:s
(3Pdc Gf Yde GdeecfGJ Ydi bSejf YGde GdCeQ hYGde GdNdb Ydi eG bGd CdG dg GdNdb hGdCeQ aYGde GdCeQ cdg MjRGJ eMVI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 /301s
(3eYLe GdeDdajf (B2 / 82s
(3cTa GdXfhf (B1 / 485s
(3TPQGJ GdPgH (B8 / 51s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs